PENGARUH PERMAINAN TANGRAM TERHADAP KREATIVITAS SISWA DALAM PEMBELAJARAN MATEMATIKA DI KELAS IV SD NEGERI 050688 SAWIT SEBERANG - Putri Theresa Theoni Filsia Br.Siagian; Nur Hudayah; Zainuddin; Elvi Mailani; Natalia Silalahi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study addresses the low level of students’ creativity in mathematics learning, particularly in geometry, caused by conventional teaching methods that limit exploration and active participation. The purpose of this research is to determine students’ creativity before and after the implementation of the Tangram game and to analyze its effect on students’ creativity in mathematics learning. This study employed a quantitative approach with a quasi-experimental method using a One Group Pretest-Posttest design. The population and sample consisted of 20 fourth-grade students of SD Negeri 050688 Sawit Seberang. Data were collected using creativity tests covering fluency, flexibility, and originality aspects. Data analysis techniques included the Wilcoxon test and N-Gain score. The results showed a significant improvement in students’ creativity after the implementation of the Tangram game, indicated by the Wilcoxon test results where the significance value was less than 0.05 (p < 0.05). Additionally, the average N-Gain score of 55.99% was categorized as moderate, indicating that the Tangram game was sufficiently effective in enhancing students’ creativity. Therefore, it can be concluded that the Tangram game has a significant effect on students’ creativity in mathematics learning.